Pengembangan Ilmu Ulumul Qur’an dalam Metode Al Ashwat terhadap Penerapan Kegiatan Tahsin Qira’ah bagi Pemula di Desa Namu Ukur Utara Kec. Sei Bingai Kab. Langkat - Syahrin Pasaribu (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2021)
Phonetics and phonology are the two branches of al-Ashwat's science that are most important in studying a language. Because if the phonetics are not in accordance with the original narrative, then the sounds of the language, phrases, words, and sentences spoken will not be understood by the other person. Or it can happen, a change in the meaning of what the speaker wants. In other words, the two sciences contribute greatly to the suitability and accuracy of sounds, words, and sentences in the language process. Understanding and mastering al-Ashwat plays an important role in these two language skills, namely maharah al-Istima' and maharah al-Kalam. With perfect comprehension and fluent pronunciation, one will be able to listen and understand the sound symbols spoken by others. This is a sign that the listening process is running smoothly and listening skills have been mastered. Also in terms of oral skills, when an Arabic speaker can understand what the other person is saying, it shows that the oral process is running smoothly and the oral skills have been mastered. Because of the important position of al-Ashwat in language learning and communication, in the process of learning al-Qur'an tahsin at all levels of education it is necessary to pay more attention to al-Ashwat. However, the reality that occurs during the teaching of tahsin al-Quran, presenting the teaching of al-Ashwat is very rare. Based on this phenomenon, this research is very useful for teachers and students to determine how to reproduce the correct Qur'an in the learning process of reading the Qur'an for beginners.